(untitled) (Educational Dimension, 2020)
In today’s classrooms, teachers are often under great pressure — they not only have to prove themselves professionally but also as strong personalities. In teachers-training courses at universities, subject-related and didactic skills are often built up intensively, but there is a lack of support for personal and social skills, planning and management skills, and development skills. Extracurricular theater projects can compensate for this shortcoming. The paper presents effects of several years of theater work on teaching students studying German as a foreign language. Theoretically, the contribution is firstly underpinned by the approach of the Canadian sociologist Erving Goffman (2003) about self-portrayal in everyday life, in which he points out a similarity between acting and social contact [3]. Second, it is based on the understanding of the “performative competence” by Wolfgang Hallet (2010). Both concepts are transferred to the social contact between teachers and learners. Extracurricular theater projects can compensate for this shortcoming. The paper presents effects of several years of theater work on teaching students studying German as a foreign language. Theoretically, the contribution is firstly underpinned by the approach of the Canadian sociologist Erving Goffman (2003) about self-portrayal in everyday life, in which he points out a similarity between acting and social contact [3]. Second, it is based on the understanding of the “performative competence” by Wolfgang Hallet (2010). Both concepts are transferred to the social contact between teachers and learners.